(untitled) (Journal of Asian Development Studies, 2014)
Improving the doing business and enhance its indices are emphasized in the fifth Article of general policies for job creation in Iran. So that this subject is considered in articles 4, 5 and 6 of continuous improvement of doing business plan in sectional and provincial perspectives. However, although the ranking of each country or region is calculated by combination of several business indices but this essential question that which of these factors is the most important to improve the business environment in each region or economic sector? is very important and there are different ways to answer it. However, accepting the centrality of the industrial sector in the economic development of Iran, it seems to answer this question is reduplicate important from the perspective of managers in this sector. Hence, this study attempts to indicate the priority of doing business indices for reform in order to implement of doing business plan in provincial level. This study is performed from the viewpoints industrial artisans, experts and managers in Yazd province as the province that has the first industrial position within provinces of Iran. Using snowball sampling and Analytic Hierarchy Process (AHP) technique, the results of this study indicate that, although there are a few differences in the ranking of business indices from the perspective of intended groups but, summing up, three indices included getting credit, trading across borders and protecting investors are considered as the main indicators of doing business reform.